2005
DOI: 10.1002/cncr.21324
|View full text |Cite
|
Sign up to set email alerts
|

The role of radiotherapy in cancer treatment

Abstract: Radiotherapy utilization rates for cancer vary widely internationally. It has previously been suggested that approximately 50% of all cancer patients should receive radiation. However, this estimate was not evidence-based. The aim of this study was to estimate the ideal proportion of new cases of cancer that should receive radiotherapy at least once during the course of their illness based on the best available evidence. An optimal radiotherapy utilization tree was constructed for each cancer based upon indica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
544
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,333 publications
(554 citation statements)
references
References 24 publications
2
544
0
8
Order By: Relevance
“…The proportion of patients prescribed with radiotherapy in this study is in line with the common benchmark reported in recent years of at least 50% of new cancer patients requiring radiotherapy [20]. Reviewing the available literature, different approaches can be found in Table 2 concerning the estimation of radiotherapy demand in different countries.…”
Section: Discussionsupporting
confidence: 80%
“…The proportion of patients prescribed with radiotherapy in this study is in line with the common benchmark reported in recent years of at least 50% of new cancer patients requiring radiotherapy [20]. Reviewing the available literature, different approaches can be found in Table 2 concerning the estimation of radiotherapy demand in different countries.…”
Section: Discussionsupporting
confidence: 80%
“…1,2 The focus of radiobiology over previous decades has been on the direct cytoreductive effect that RT exerts on cancer cells by inducing DNA damage and only relatively recently have the effects of RT on tumour vasculature, stroma and the immune system received more attention. RT is known to have a number of effects on the generation of tumour-specific immunity, which include enhanced antigen release, expression of Natural killer receptor G2D (NKG2D) ligands, production of Type I Interferon (IFN) and complement, increased major histocompatibility complex and neoantigen expression and the induction of immunogenic cell death (ICD).…”
Section: The Interplay Of Radiotherapy With the Tumour Microenvironmentmentioning
confidence: 99%
“…Radiotherapy is one of the most effective methods for the treatment of cancer (Njeh 2008) with an estimate of 52% of cancer patients benefitting from it (Delaney et al 2005). With the aging population, cancer incidence and mortality are expected to increase (Yancik and Ries 2004).…”
Section: Introductionmentioning
confidence: 99%